Computer-based documentation and bedside terminals. - Merkouris AV (Journal of Nursing Management, 1995)
Rising health care costs and the need for enhancing the quality of clinical care are concerns of hospitals throughout the world. Documentation consumes excessive amounts of nursing time and directly influences the quality of clinical practice, research, administration and education. Recent developments in information technology have offered many alternatives to traditional systems of documentation. Many hospitals have installed bedside terminals, but only few have conducted and published studies regarding their implementation. Most of the studies come from the US and report improved quality of care and reduction of nursing expenses. All the relevant studies have design, sample and methodological problems. There is a need for additional systematic studies to prove the actual benefits of the bedside terminals and link them with the outcomes of care. This paper intends to review the literature and discuss the installation, use, results and future directions of the bedside terminals.